2018
DOI: 10.1103/physrevb.97.125104
|View full text |Cite
|
Sign up to set email alerts
|

Free-fermion descriptions of parafermion chains and string-net models

Abstract: Topological phases of matter remain a focus of interest due to their unique properties -fractionalisation, ground state degeneracy, and exotic excitations. While some of these properties can occur in systems of free fermions, their emergence is generally associated with interactions between particles. Here we quantify the role of interactions in general classes of topological states of matter in all spatial dimensions, including parafermion chains and string-net models. Using the interaction distance [Nat. Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…(More precisely, for any fixed configuration of m a 's the Hamiltonian is quadratic.) This observation connects with the recent work of Meichanetzidis et al [26] that inferred free-fermion eigenstates from an analytic solution of the f = 0 fixed point combined with an interesting numerical diagnostic for the general case [69]. In terms of the clock-model states in Eq.…”
Section: A Hamiltonianssupporting
confidence: 87%
See 1 more Smart Citation
“…(More precisely, for any fixed configuration of m a 's the Hamiltonian is quadratic.) This observation connects with the recent work of Meichanetzidis et al [26] that inferred free-fermion eigenstates from an analytic solution of the f = 0 fixed point combined with an interesting numerical diagnostic for the general case [69]. In terms of the clock-model states in Eq.…”
Section: A Hamiltonianssupporting
confidence: 87%
“…Second, Ref. [26] used complementary analytical and numerical methods to infer that the eigenstates of certain Z 4 parafermion chains can be described in terms of free fermions. Third, Zhang and Kane [27] and Orth et al [28] showed that proximitized edge states of a two-dimensional quantum-spin-Hall insulator can support zero modes reminiscent of Z 4 parafermions (see also Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The condition D F = 0 corresponds to a system that can be exactly described by free fermions, while D F = 3 − 2 √ 2 is the maximum distance a density matrix can have from a free description. Note that even this value can be attained only for asymptotically large systems [50].…”
Section: General Properties Of Interaction Distancementioning
confidence: 97%
“…Importantly, the optimal free state σ, i.e., the one with the smallest distance from ρ, does not need to be expressed in terms of the original degrees of freedom, c j , that define the Hamiltonian. Moreover, in general the optimal free state may not be unique, although in many cases it was indeed found to be 3,32 . When ρ is chosen to be the reduced density matrix, D F measures the distance of the entanglement spectrum, corresponding to the given state |ψ and the given partition, from the closest possible freefermion entanglement spectrum, {E f k }, given by Eq.…”
Section: B Short and Long Distance Behavioursmentioning
confidence: 99%